Shedding light on biochemical changes in single neuron-like pheochromocytoma cells following exposure to synchrotron sourced terahertz radiation using synchrotron source Fourier transform infrared microspectroscopy - Palalle G. Tharushi Perera; Jitraporn Vongsvivut; Denver Linklater; Zoltan Vilagosh; Dominique Appadoo; The Hong Phong Nguyen; Mark J. Tobin; Rodney Croft; Elena P. Ivanova (Journal of Synchrotron Radiation)
Synchrotron sourced Fourier transform infrared (SS FTIR) microspectroscopy was employed to investigate the biological effects on the neuron-like pheochromocytoma (PC 12) cells after exposure to synchrotron sourced terahertz (SS THz) radiation. Over 10 min of exposure, the PC 12 cells received a total energy of 600 J m2, with a total incident power density of ∼1.0 W m−2 (0.10 mW cm−2) at the beam extraction port (BEP) of the THz beamline at the Australian Synchrotron. To investigate the metabolic response of PC 12 cells after synchrotron THz radiation exposure, we utilized the FTIR microscope at the Infrared Microspectroscopy IRM beamline, which offers high photon flux and diffraction-limited spatial resolution enabling the detection of functional group variations in biological molecules at a single-cell level. Principal component analysis (PCA) based on the SS FTIR spectral data revealed a distinct separation of SS THz-exposed and control (non-exposed) cells. According to the PCA loadings, the key changes in the exposed cells involved lipid and protein compositions as indicated by the stretching vibrations of CH2/CH3 groups and amide I/II bands, respectively. An increase in lipids, such as cholesterol, or notable changes in their compositions and in some protein secondary structures were observed in the SS THz-exposed cells. The PCA analysis further suggests that PC 12 cells might maintain cell membrane stability after SS THz irradiation through higher volumes of cholesterol and cell morphology via regulation of the synthesis of cytoskeleton proteins such as actin-related proteins. The outcome of this study re-emphasized the exceptional SS FTIR capability to perform single-cell analysis directly, providing (i) unique biological information on cell variability within the population as well as between different groups, and (ii) evidence of molecular changes in the exposed cells that could lead to a deeper understanding of the effect of THz exposure at a single-cell level.